Adolescent pregnancy, maternal and child anaemia: Empirical analysis from India, Bangladesh, and Nigeria - Anu Rammohan; Hoi Chu; Niyi Awofeso; Srinivas Goli (Maternal and Child Nutrition)
Abstract Early childbearing poses several potential risks to maternal and child health. This paper empirically analyses the association between teenage pregnancy and child nutritional status, maternal and child anaemia in three countries (Nigeria, India and Bangladesh) that account for the highest proportion of teenage births and/or total number of malnourished teenage mothers and children. Data were sourced from nine waves of Demographic and Health Surveys conducted in Bangladesh, India, and Nigeria from 2005–2018, covering a sample of 27,705 children from Bangladesh, 266,308 children from India and 54,719 children from Nigeria. Our outcome measures of maternal and child nutrition include (i) a composite measure of anthropometric failure for children (CIAF), (ii) maternal anaemia, (iii) childhood anaemia, and (iv) anaemia in maternal–child pairs. Using multivariate regression analysis, we examine the associations between early childbirth, child nutrition, and maternal and child anaemia, controlling for an array of household‐level socioeconomic and demographic characteristics. Across all three countries, the prevalence of CIAF (childhood anthropometric failure) is significantly higher among children born to women aged below 17 at first birth. We further find that early pregnancy and childbearing are associated with significantly higher rates of severe/moderate anaemia among both mothers and children in Bangladesh and Nigeria. In the three countries studied, the proportions of teenage mothers with vulnerable socioeconomic status and suboptimal pre‐conception care are relatively high, which raises the risk of maternal and child morbidity as well as mortality.